Hesperis sivasica (Brassicaceae), A new crucifer species from inner Anatolia - Özüdoğru, Bariş; Altinözlü, H.; Özgi̇şi̇ Kurtuluş (Phytotaxa, 2024)
Hesperis sivasica, from the Kangal district of Sivas Province in inner Anatolia (Türkiye), is described as a new species based on morphological and molecular evidence. Although it is not morphologically closely related to the known species of Hesperis, it resembles H. kotschyi in trichome types but differs from it in pedicel, flowers, and fruit characteristics. In molecular phylogenetic analyses based on the Nuclear-encoded ribosomal internal transcribed spacer (ITS) region, H. sivasica belongs to the same clade as H. bottae and H. thyrsoidea, but it is easily distinguishable from both species based on life form, trichome types, flowers, and fruit characters. Diagnostic morphological characters, full description, SEM microphotographs, and detailed field photographs are provided. Remarks on the new species’ habitat, ecology, phenology, distribution, and conservation status are also given.